Analisis Yuridis Pasal 330 Ayat (3) Kuhperdata dalam Proses Perwalian Anak Kandung di Bawah Umur yang Melakukan Perbuatan Hukum - Agung Maradona (Universitas Bandar Lampung (UBL), 2018)
An underage child who has never done a marriage requires a guardian to take care of theirself and their property and the guardianship is automatically in the hands of their parents. The research method uses a normative and empirical juridical approach. The results of the study indicate that the submission of an application as guardian of a biological child who is still underage in carrying out a legal act, in this case the sale of a plot of land and building, the applicant should not have to submit a request to be the guardian of a minor The process of guardianship of underage children who carry out legal acts in this case the sale of land and buildings, guardianship carried out by their parents is when they are young, they are not yet smart and understand things related to property expenditure.